2017
DOI: 10.18632/oncotarget.18606
|View full text |Cite
|
Sign up to set email alerts
|

Increased intraepithelial CD3+ T-lymphocytes and high PD-L1 expression on tumor cells are associated with a favorable prognosis in esophageal squamous cell carcinoma and allow prognostic immunogenic subgrouping

Abstract: Esophageal squamous cell carcinoma (ESCC) is the most common esophageal cancer associated with poor prognosis and additional therapeutic strategies must be implemented to optimize ESCC treatment. Meanwhile, the important biologic role and potential prognostic and therapeutic implications of a tumors immunologic microenvironment (IM) have been recognized in various cancers.In order to investigate the contexture and the prognostic relevance of the IM in ESCC, we immunohistochemically evaluated the extent of over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 44 publications
(64 reference statements)
8
52
1
Order By: Relevance
“…The univariate and multivariate analyses of therapy-naive tumors revealed that PD-L1-positive ESCC was associated with favorable OS and DFS. This result concurred with that of previous studies that demonstrated favorable prognosis of PD-L1 expression in surgically resected ESCCs without preoperative or neoadjuvant treatment [21][22][23]26]. In this study, high PD-L1 expression was prevalent among light or nonsmoker patients without lymph node metastasis and with high TILs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The univariate and multivariate analyses of therapy-naive tumors revealed that PD-L1-positive ESCC was associated with favorable OS and DFS. This result concurred with that of previous studies that demonstrated favorable prognosis of PD-L1 expression in surgically resected ESCCs without preoperative or neoadjuvant treatment [21][22][23]26]. In this study, high PD-L1 expression was prevalent among light or nonsmoker patients without lymph node metastasis and with high TILs.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, several studies have reported that the frequencies of tumor cells exhibiting PD-L1 expression in ESCC range from 18.4-79.7%, which might be attributable to the differences in the antibodies used, interpretation criteria, specimen types affected by neoadjuvant therapy, and the geographic or racial characteristics [18][19][20][21][22][23][24]. In this study, PD-L1-positive tumors were observed in 35.9% of cases, which is highly consistent with a previous Korean population-based study (33.5%) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that in ltrating bystander CD8 + T cells, which do not recognize tumor antigens and thus have no ability to kill neoplastic cells, exist in human lung and colorectal tumors. 21 For in ltrating CD3 + T cells, our results are consistent with the only available study 19 for ESCC. Both studies demonstrate that CD3 + T cell in ltration is an independent favourable prognostic factor.…”
Section: Discussionsupporting
confidence: 87%
“…For in ltrating CD8 + T cells, our results are consistent with a previous study, 19 but inconsistent with two other studies. 16,17 This inconformity suggests that in ltrating CD8 + T cells in esophageal tumors include different functional subgroups that are unable to be solely identi ed by IHC.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation